Chemorheological Monitoring of Cross-Linking in Slide-ring Gels Derived From α-cyclodextrin Polyrotaxanes - Dikshit , Karan; Bruns , Carson J. (Frontiers in Chemistry, 2022)
Despite hundreds of studies involving slide-ring gels derived from cyclodextrin (CD)-based polyrotaxanes (PRs), their covalent cross-linking kinetics are not well characterized. We employ chemorheology as a tool to measure the gelation kinetics of a model slide-ring organogel derived from α-cyclodextrin/poly (ethylene glycol) PRs cross-linked with hexamethylenediisocyanate (HMDI) in DMSO. The viscoelastic properties of the gels were monitored in situ by small-amplitude oscillatory shear (SAOS) rheology, enabling us to estimate the activation barrier and rate law for cross-linking while mapping experimental parameters to kinetics and mechanical properties. Gelation time, gel point, and final gel elasticity depend on cross-linker concentration, but polyrotaxane concentration only affects gelation time and elasticity (not gel point), while temperature only affects gelation time and gel point (not final elasticity). These measurements facilitate the rational design of slide-ring networks by simple parameter selection (temperature, cross-linker concentration, PR concentration, reaction time).